Logic programming and knowledge representation—The A-Prolog perspective - Gelfond, Michael; Leone, Nicola (Artificial intelligence, 2002)
In this paper we give a short introduction to logic programming approach to knowledge representation and reasoning. The intention is to help the reader to develop a ‘feel’ for the field's history and some of its recent developments. The discussion is mainly limited to logic programs under the answer set semantics. For understanding of approaches to logic programming built on well-founded semantics, general theories of argumentation, abductive reasoning, etc., the reader is referred to other publications.